Gap Junctions Mediate Human Immunodeficiency Virus-Bystander Killing in Astrocytes - Eugenin, Eliseo A. (Society for Neuroscience, 2007)
Human immunodeficiency virus (HIV) entry into the CNS is an early event after infection, resulting in neurological dysfunction in a significant number of individuals. As people with acquired immunodeficiency syndrome (AIDS) live longer, the prevalence of cognitive impairment is increasing, despite antiretroviral therapy. The mechanisms that mediate CNS dysfunction are still not completely understood, and include inflammation, viral presence, and/or replication. In this report, we characterize a novel role of gap junctions in transmitting and thereby amplifying toxic signals originating from HIV-infected astrocytes that trigger cell death in uninfected astrocytes. HIV-infected astrocytes were resistant to apoptosis; however, uninfected astrocytes forming gap junctions with infected astrocytes were apoptotic. Gap junction blockers abolished apoptosis in uninfected astrocytes, supporting the role of these channels in amplifying cell death. Our findings describe a novel mechanism of toxicity within the brain, triggered by low numbers of HIV-infected astrocytes and amplified by gap junctions, contributing to the pathogenesis of NeuroAIDS.